Pycnogenol® Induces Browning of White Adipose Tissue through the PKA Signaling Pathway in Apolipoprotein E-Deficient Mice - Huiying Cong; Wenxia Zhong; Yiying Wang; Shoichiro Ikuyama; Bin Fan; Jianqiu Gu (Journal of Diabetes Research)
Beige adipocytes in white adipose tissue (WAT) have received considerable recognition because of their potential protective effect against obesity. Pycnogenol (PYC), extracted from French maritime pine bark, has anti-inflammatory and antioxidant properties and can improve lipid profiles. However, the effect of PYC on obesity has never been explored. In this study, we investigated the effects of PYC on obesity and WAT browning in apolipoprotein E- (ApoE-) deficient mice. The results showed that PYC treatment clearly reversed body weight and the mass of eWAT gain resulting from a high-cholesterol and high-fat diet (HCD), but no difference in food intake. The morphology results showed that the size of the adipocytes in the PYC-treated mice was obviously smaller than that in the HCD-fed mice. Next, we found that PYC upregulated the expression of genes related to lipolysis (ATGL and HSL), while it decreased the mRNA level of PLIN1. PYC significantly increased the expression of UCP1 and other genes related to beige adipogenesis. Additionally, PYC increased the expression of proteins related to the protein kinase A (PKA) signaling pathway. The findings suggested that PYC decreased obesity by promoting lipolysis and WAT browning. Thus, PYC may be a novel therapeutic target for obesity.